2021
DOI: 10.1016/j.cegh.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: District level vulnerability assessment in India

Abstract: Objectives COVID-19 Pandemic has brought a threatening challenge to the world and as well as for Indian society and economy. In India, it has become a public health disaster and its' intensity increasing continuously. For the disaster risk reduction, and capacity building against the COVID-19 pandemic understanding of the relationship between socio-environmental conditions with the pandemic is very necessary. The objective of the present work is to construct a socio-environmental vulnerability ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 43 publications
2
70
1
4
Order By: Relevance
“…At the onset of the COVID-19 pandemic, India imposed world’s strictest nationwide lockdown beginning from March 25, 2020 [ 39 ], But, as of April 10, 2021, India was the third leading country after USA and Brazil’s identified cases [ 40 ]. Like several other parts of the world, India has been experiencing a massive surge of COVID-19 cases and deaths [ 41 43 ]. The second wave has started in the middle of March, 2021 and recorded highest number of cases (144,829) on April 09, 2021 [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the onset of the COVID-19 pandemic, India imposed world’s strictest nationwide lockdown beginning from March 25, 2020 [ 39 ], But, as of April 10, 2021, India was the third leading country after USA and Brazil’s identified cases [ 40 ]. Like several other parts of the world, India has been experiencing a massive surge of COVID-19 cases and deaths [ 41 43 ]. The second wave has started in the middle of March, 2021 and recorded highest number of cases (144,829) on April 09, 2021 [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the confirmed cases in Ramallah & Al-Bireh are very high whereas the CVI is relatively high. However, the number of confirmed cases is highly related to socio-economic conditions such as poor households [ 19 ] employment [ 43 ], car ownership [ 26 ], and household density [ 44 ]. Thus, the obtained CVI values do not reflect the actual number of the confirmed cases in all of the West Bank governorates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the relaxation phase of domestic transportation (especially railways) from November 2020 up to almost mid of April made the situation favourable for rapid infection spread. A recent study revealed the composite analysis based on socio-economic-political parameters at the district level to construct a new Socio-Economic Vulnerability Index ( Sarkar and Chouhan, 2021 ). The index indicated the high vulnerability of North-West Delhi, Central Delhi, Kolkata, Mumbai and Ghaziabad.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic has resurfaced in India in the form of a hard-hitting second wave. The COVID-19 has brought a threatening challenge to Indian society and the economy ( Sarkar and Chouhan, 2021 ). India's devastating second wave of COVID-19 has overwhelmed its health system and the country ( Ranjan, 2020 , Ghosh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%